TINJAUAN PENANGANAN SAMPAH DI PASAR KASOMALANG KECAMATAN KASOMALANG KABUPATEN SUBANG PADATAHUN 2022 - Bambang Purnama, Lubis; Sadam Arafat, Yaser (Poltekkes Kemenkes Bengkulu, 2023)
The market is one place that produces waste. Kasomalang Market generates 265.23 Kg/day of waste generation, and if it is estimated that waste generation per trader at Kasomalang Market reaches 1.09 Kg/person/day. The purpose of this research is to know the description of waste handling. This research is descriptive with a survey method using observation and interview techniques. The sample in this study included 5 trash bins, 2 carts, 1 TPS, 71 traders and 5 garbage workers at Kasomalang Market. The results obtained from observations and interviews were then analyzed using univariate techniques. Based on the results of observations on waste handling, for traders at the container stage 66.66% did not meet the requirements, for waste workers at the transportation stage 57.14% fulfilled the requirements. for the results of the observation that 80% of the trash bin facilities did not meet the requirements as well as the facilities for the temporary collection site (TPS) of 40% did not meet the requirements and the waste transportation equipment (cart) did not meet the requirements of 100%. Meanwhile, the knowledge of waste workers can be categorized as sufficient, 70%, and 71.2% for traders. Overall, waste management and facilities at Kasomalang Market do not meet the requirements. It is recommended that Kasomalang Market managers procure trash cans, personal protective equipment (PPE), trash carts and garbage containers